Module Development For Enhancing Islamic Integrated Personality Among Muslim Students At Universiti Sultan Zainal Abidin Terengganu - Rahimah, Embong; Azhar, Yaacob; Nik Murshidah, Nik Din; Normila, Noruddin@Che Ahmad; Nur Anis, Abdullah (2015)
This paper aims to develop a standardized module to be applied in a special program for enhancing Muslim students’ personality at Universiti Sultan Zainal Abidin. There are four distinguished features that characterize a person with an Islamic integrated personality (IIP). The first is good servant (ábd al-salih) who possesses high spirituality and good moral characters. The second is becoming a good vicegerent (khalifah Allah) who is globally competent. The third is having high intellectual knowledge and professional acumen. The fourth is a living Qur'an (hujjah al-Islam). The noble aim to produce IIP may be realized through a comprehensive personality development that comprises all domains of spirituality, morality, intellectuality, physical, professionalisme as well as individual and social benefits. To develop the whole personality of students in classrooms at a higher institution is almost impossible for it involves many constraints. However, this could be possible if program based on the integration of all personality domains could be designed and developed. This program can be integrated as a part of extracurricular activities for students. Developmental research method is employed to develop module for IIP enhancement program. Observations, fasilitators’ journals and questionnaires had been used to collect data to evaluate the impact of the module and the whole program. This developmental research project attempts to develop module for enhancement of IIP that can be implemented in extracurricular activities among Muslim students in higher instutions in Malaysia.